Investigation of ice accretion effect on the aerodynamic characteristics of a wind turbine blade tip after a short icing event - Kangash, A I; Pankratov, E V; Kosarev, I A; Maryandyshev, P A; Virk, M S (IOP conference series. Earth and environmental science, 2023)
The paper investigates the flow behavior near the NACA 64-618 airfoil profile of the blade tip section of a wind turbine for electric power production after a short icing event. The flow simulation considering the rotation speed of the wind turbine blade is performed to assess the effect of icing on the aerodynamic characteristics. Degradation of aerodynamic characteristics affects the electrical energy production of the wind turbine. The aerodynamic lift and drag coefficients are calculated for different angles of attack. The flow velocity fields near the airfoil are analyzed. The pressure coefficient distributions along the profile surface are obtained. The points of flow stall and changes of aerodynamic characteristics at different angles of attack are determined.